2012
DOI: 10.4049/jimmunol.1103072
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenase-1 Promotes the Persistence ofLeishmania chagasiInfection

Abstract: Visceral leishmaniasis (VL) remains a major public health problem worldwide. This disease is highly associated with chronic inflammation and a lack of the cellular immune responses against Leishmania. It is important to identify major factors driving the successful establishment of the Leishmania infection to develop better tools for the disease control. Heme oxygenase-1 (HO-1) is a key enzyme triggered by cellular stress, and its role in VL has not been investigated. In this study, we evaluated the role of HO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
122
1
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(137 citation statements)
references
References 68 publications
10
122
1
4
Order By: Relevance
“…Additionally, we observed a significant increase in HO-1 expression in both murine macrophage RAW264.7 and hepatoma Hepa1-6 cells (unpublished data). This is consistent with previously published studies demonstrating an upregulation of HO-1 mRNA and/or protein expression in response to bacterial (29,(40)(41)(42)(43)(44)(45) or parasitic (26,27,46) infections and might be a general response of infected host cells.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Additionally, we observed a significant increase in HO-1 expression in both murine macrophage RAW264.7 and hepatoma Hepa1-6 cells (unpublished data). This is consistent with previously published studies demonstrating an upregulation of HO-1 mRNA and/or protein expression in response to bacterial (29,(40)(41)(42)(43)(44)(45) or parasitic (26,27,46) infections and might be a general response of infected host cells.…”
Section: Discussionsupporting
confidence: 82%
“…Mortality in human melioidosis was also predicted by the presence of serum bilirubin among other factors (64), which may serve as a marker for increased HO-1 activity and inducibility in tissues (65). Consistent with our results, increased concentrations of HO-1 have also been found during Leishmania infection of mice, and elevated serum levels of TNF-a have been associated with human visceral leishmaniasis (46). The high amounts of cytokines might be a secondary effect of elevated bacterial counts in vivo and can induce higher levels of HO-1 as a counterregulatory response.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our study suggests no clear HO-1 is also a stress-responsive enzyme, and induction of HO-1 results in the catabolism of prooxidant heme to biliverdin and bilirubin, which are potent antioxidants [25]. Many anti-inflammatory properties are attributed to HO-1 and the beneficial effects of HO-1 have been reported in various models of inflammation, including pleural inflammation, renal injury and small bowel ischemia [11,25,38,48,63] showed that L. pifanoi and L. chagasi infections trigger an increase in HO-1 levels in cultures of macrophages and serum from patients with visceral leishmaniasis. In our study, HO-1 was detected in the footpad and rump models.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, it is well known that the inducers of HO-1 expression inhibits the expression of the inflammatory genes (cyclooxygenase-2 and inducible nitric oxide synthase), and subsequently decreases PGE 2 and NO production (Oh et al, 2006;Suh et al, 2006). It also was recently reported that the HO-1 system provides a therapeutic effect in many experimental pathological conditions (Bonelli et al, 2012;Farombi and Surh, 2006;Luz et al, 2012). In oxidative injury and inflammation conditions, an increase in the synthesis of the HO-1 gene is linked to the transcription factors NFkB, Nrf2, and AP-1 (Paine et al, 2010;Srisook et al, 2005;Surh et al, 2009).…”
Section: Introductionmentioning
confidence: 99%